Macedonia through the theory of territorial integration: one hundred years before - Toni MIleski (Bezbednosni Dijalozi, 2013)
This text, through political-geographic and geopolitical analysis, deals with a problem that was relevant more than one hundred years ago, and it refers to the situations that reflect through the centripetal and the centrifugal forces that are fundamental in the creation of the states. Basically, the paper analyzes the situations on the territory of Macedonia during the Ottoman Empire, until they break out of the Balkan Wars and the territorial partition of Macedonia. The theoretical basis of the political-geographic analysis relies on Richard Hartshorne’s theory of territorial integration, a model which, with certain modifications, will be applied for the territory of Macedonia under Ottoman rule, and a model which enables specific case studies.